Woodrose Mountain - Thayne, RaeAnne (Don Mills, Ont. : HQN Books, 2012)
Seeking a quieter life, physical therapist Evie Blanchard puts her plans on hold when single dad Brodie convinces her to help his injured daughter, Taryn, and she finds it hard to keep an emotional distance from Brodie and Taryn.
Keywords: Physical therapists; Fiction; Single fathers -- Fiction; Small cities; Fiction; Interpersonal attraction; Fiction; Colorado -- Fiction; Romance fiction